Desempenho energético de diferentes motores geradores em sistemas de geração distribuída de energia elétrica a biogás - Souza, Juliano de (2023)
This work addresses the evaluation of biogas electricity generator engines for distributed electricity generation in rural areas. Different generator engines (MG) were studied in order to define the best MG configuration for a distributed generation unit in a swine farm where there is availability of biogas produced in plug flow biodigesters (piston flow) resulting from waste treatment. Five (05) biogas engines were evaluated, three (03) of which were produced by the company Biogás Motores Estacionários LTDA (BIOGÀS) and the other two (02) by other companies. The specific consumption, efficiency of the five (05) five MG and the emissions of (04) four MG were obtained, basically NOx, HC, CO and CO2 gases, varying the load of the MG (in kW), of a value minimum to a maximum compatible value for each machine. For (02) two MG produced by BIOGÁS, engine D and E, their performance was determined by varying the load (C), the ignition advance (P) and the air-fuel ratio (λ). For this, the consumption of biogas in the generator engines, the generation of electricity in the generator and the concentration of methane in the biogas were measured. As a result, it was observed that the engine with the highest efficiency was the German technology engine, with an efficiency of 27% at maximum load (75 kW), due to the most advanced combustion technology. Among the MG produced by BIOGÁS, the D engine had the best efficiency, 21%. On the other hand, engine E, also produced by BIOGÀS, showed slightly lower efficiency than engine D, 19% at maximum load (50 kW). In addition to emitting less HC, CO2 and CO compared to the others, in terms of NOx it emits more than engine D. On the other hand, it was concluded that engine E would be the best, as its capital cost is lower than engine D and it can operate in plants with less biogas availability at maximum load in finishing pig farms, with fattening up to 5000 pigs